Colorectal Cancer Patients In A Tertiary Referral Centre In Malaysia: A Five Year Follow-up Review - Mohd Radzniwan A Rashid; Aznida Firzah Abdul Aziz; Saharuddin Ahmad; Shamsul Azhar Shah; Ismail Sagap (Asian Pacific Journal of Cancer Prevention, 2024)
Volume: 10 Issue: 6